Comparative Analysis of the Implementation of Formative and Summative Assessment: A Case Study of the Shift in Assessment Practices from the 2013 Curriculum to the Merdeka Curriculum among Elementary School Teachers at Hasanah Quranic School (HQS) Bekasi - Iyan Nurhasni Ahya; Hery Setiyatna (Pasundan Social Science Development, 2026)
This study examines the shift in assessment paradigms and practices among elementary school teachers following the transition from the 2013 Curriculum (Kurikulum 2013/K-13) to the Merdeka Curriculum in Indonesia. The study focuses on two issues: the changing orientation from summative assessment toward formative assessment, and the implementation challenges associated with project-based assessment, particularly the Projek Penguatan Profil Pelajar Pancasila (P5). A descriptive survey with a mixed-method design was conducted at Hasanah Quranic School (HQS) Bekasi. Quantitative data were collected using a five-point Likert-scale questionnaire completed by 17 teachers, while qualitative data were obtained through open-ended responses and analyzed thematically. The findings indicate that teachers demonstrated a relatively strong conceptual understanding of formative assessment as a tool for improving learning (M = 3.88) and reported frequent use of feedback practices (M = 3.82). However, teachers’ understanding of P5 assessment methodology remained at a neutral level (M = 3.29), suggesting methodological uncertainty in assessing project-based learning through qualitative and narrative evidence. Qualitative findings confirmed three major challenges: the demand for teacher creativity and innovation, instability in report-card administration systems, and the suboptimal implementation of P5. The study concludes that the philosophical orientation of formative assessment has been generally accepted by teachers, but implementation quality still depends on practical training, shared assessment instruments, systematic documentation of learning evidence, and consistent school-level guidance for P5 reporting